2009
DOI: 10.1186/1475-2891-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of the diet with the functional fiber PolyGlycoplex®is well tolerated by healthy subjects in a clinical trial

Abstract: Background: The relationship of dietary fiber to overall health is of great importance, as beneficial effects have been demonstrated with the use of fiber from diverse sources, some traditional, other novel. PolyGlycopleX ® (PGX ® ) is a unique proprietary product composed of three water-soluble polysaccharides, that when processed using novel technology give rise to a final product -a soluble, highly viscous functional fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 29 publications
2
49
1
Order By: Relevance
“…No subjects withdrew from the study and the product was well tolerated as previously reported (Carabin et al, 2009). The control group (11 males and 16 females) had a mean age of 30.9 ± 10.8 and BMI of 22.8±2.4 kg/m 2 .…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…No subjects withdrew from the study and the product was well tolerated as previously reported (Carabin et al, 2009). The control group (11 males and 16 females) had a mean age of 30.9 ± 10.8 and BMI of 22.8±2.4 kg/m 2 .…”
Section: Resultsmentioning
confidence: 70%
“…There were also significant negative correlations between ghrelin and insulin at V1 and V2 (r ¼ À0.28, P ¼ 0.038 and r ¼ À0.31, P ¼ 0.022 respectively) and between ghrelin and HOMA-IR at V1 and V2 (r ¼ À0.27, P ¼ 0.052 and r ¼ À0.28, P ¼ 0.041, respectively). Carabin et al (2009) previously showed that 3 weeks of PGX supplementation is well tolerated by healthy subjects. In this study, we report that PGX is able to increase levels of fasting PYY compared with control product and this is statistically significant in participants with a BMIo23 kg/m 2 .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations